PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PEMAHAMAN PESERTA DIDIK PADA MATERI PENYAJIAN DATA DALAM BENTUK DIAGRAM - Gabriela Hariati Darin; Raoda Ismail; Elsi Sirampun; Bettisari Napitupulu; Pitriana Tandililing (Journal of Research in Science and Mathematics Education, 2026)
Purpose: Conceptual understanding is fundamental to mathematics learning because it enables students to interpret and apply mathematical concepts meaningfully. In learning data presentation, students are expected to construct and interpret statistical diagrams. However, preliminary observations at YPK Hedam Abepura Junior High School revealed that many students experienced difficulties in these tasks, while teacher-centered instruction limited active participation. This study explored the implementation of the Jigsaw cooperative learning model and its contribution to students’ conceptual understanding of data presentation in diagram form. Methodology: A descriptive qualitative design was employed involving one mathematics teacher and 23 seventh-grade students. Data were collected through classroom observations, interviews, individual tests, and documentation. Trustworthiness was established through data source and method triangulation, and data were analyzed using the interactive model of Miles, Huberman, and Saldaña. Findings: The findings indicate that the Jigsaw cooperative learning model was implemented systematically in accordance with its instructional procedures. The use of home and expert groups promoted active participation, collaboration, responsibility, self-confidence, curiosity, and careful data interpretation. Individual test results showed that 18 of the 23 students achieved the minimum mastery criterion, whereas five students encountered difficulties, particularly in constructing pie charts. Significance: Overall, the findings suggest that the Jigsaw cooperative learning model enhances students’ conceptual understanding by facilitating collaborative knowledge construction through peer discussion and shared learning responsibilities. Nevertheless, because the study involved a single class and was conducted over only two instructional sessions, the findings should be interpreted cautiously when considering their transferability to other educational contexts.